Gallium, germanium, indium, and other trace and minor elements in sphalerite as a function of deposit type — A meta-analysis - Frenzel, Max; Hirsch, Tamino; Gutzmer, Jens (Ore geology reviews, 2016)
While a significant amount of analytical data on trace and minor element concentrations in sphalerite has been collected over the last six decades, no meta-analysis of this data has ever been conducted. In this study, the results of such an analysis are presented. While the study focusses on Ga, Ge and In, data for six other elements (Ag, Cd, Co, Cu, Fe and Mn) was also included. The results show that there are systematic, statistically significant differences in the mean concentrations of Fe, Ga, Ge, In and Mn in sphalerite from different deposit types, while Cd and Cu concentrations show no such differences, and Ag and Co concentrations are only significantly different for vein-type deposits. A principal component analysis demonstrates that the differences between deposit types are approximately one-dimensional, being expressible in terms of a single number. This number correlates strongly with the homogenisation temperature of fluid inclusions (R2=0.82, p<2×10−16). It may be expressed as follows:PC1*=lnCGa0.22·CGe0.22CFe0.37·CMn0.20·CIn0.11 with Ga, Ge, In and Mn concentrations in ppm, and Fe concentration in wt.%. The relationship is sufficiently strong to be used as a geothermometer (GGIMFis). The empirical relationship between PC 1* and the homogenisation temperature, T, is:T°C=54.4±7.3⋅PC1*+208±10. Our results indicate a strong control of sphalerite chemistry by fluid temperature, particularly for the concentrations of Ga (R2~0.40), Ge (R2~0.65), Fe (R2~0.30) and Mn (R2~0.60), and to a lesser degree In (R2~0.10). The concentrations of Ag, Cd, Co and Cu appear to be independent of temperature. As a consequence of the strong temperature control on PC 1*, metamorphic overprinting of Pb–Zn deposits, even by lower greenschist facies events, may lead to significant changes in sphalerite composition, namely a relative decrease in Ga and Ge concentrations, and increase in Fe, Mn and, to a lesser degree, In concentrations. The closure temperature of sphalerite in regional metamorphic events appears to be around 310±50°C, such that higher-grade events will not be reflected in its composition. Factors other than temperature, such as differences in fluid salinity or source-rock composition, do not appear to be responsible for differences between deposit types, but rather appear to cause differences between individual deposits. Particularly, the Cu activity in ore-forming systems appears to have a strong influence on In concentrations in sphalerite. The observed trends in sphalerite compositions provide a useful tool for future studies of different types of Pb–Zn deposits, as well as for mineral exploration. They should be particularly relevant for the identification of new resources of Ga, Ge and In. [Display omitted] •We quantify the differences in trace element concentrations of sphalerites from different types of Pb-Zn deposits.•These differences lie along a single dimension in the nine-dimensional sample space defined by the data.•Using a compilation of fluid inclusion data we show that this dimension reflects changes in formation temperature.•While the concentrations of Mn, Fe, and to a lesser degree In, increase with temperature, those of Ga and Ge decrease.•Based on the strong correlation of Ga, Ge, In, Mn and Fe with temperature we suggest a new sphalerite thermometer – GGIMFis.